Effects of Audio-Visual Media on Academic Achievement of Senior Secondary Schools Islamic Studies Students in Kwara State, Nigeria - Issa Muhammad-Jamiu (Journal of Digital Learning and Education, 2023)
The Nigeria government provide audio visual media for their teachers for the effective teaching and learning process of the all subjects. Academic achievement is the performance of students in the subjects they study in the school. This determines the pupils’ status in the class. This gives children an opportunity to develop their talents, improve their grades and prepare for future academic challenges. The above fact calls for investigation on the effects of audio-visual media on academic achievement of senior secondary schools’ Islamic Studies students in Kwara State, Nigeria. This study adopted a quasi-experimental research design. the specific research design used was pretest and posttest, non-equivalent control group design. The population for this study was one hundred and fifty-seven (157) Islamic studies students in Ilorin South, Kwara State, Nigeria. Simple randomly sampling technique was using to select 50 SS II Islamic Studies students in senior secondary school in Ilorin South, Kwara State, Nigeria. This study also used  25 students for experimental group and 25 students for control group. Questionnaire was used for data analysis. Hypotheses were tested using t-test statistical package at an alpha level of 0.05. The finding of the study revealed that there was a significant difference in the academic achievement of private and public senior secondary school students taught Islamic studies using audio-visual media and those taught using chart. The result also revealed that there was no significant difference in academic achievement of male and female students taught Islamic studies using audio-visual media and those taught using chart. Also, there was no significant difference in academic achievement of rural and urban senior secondary school students taught Islamic studies using audio-visual media and those taught using chart This study concluded that audio-visual media has a significant effect on academic achievement of senior secondary school Islamic Studies students.  The study recommended that  infrastructure of the schools should be designed in such a way that of audio-visual aids  could be used successfully.